The business value of information technology in local government : case studies from Sedibeng and Emfuleni - Mokoena, Naledi S. (North-West University, 2005)
Organisations spend between five and ten percent of their revenue on information technology (IT). With this capital expenditure, there is a growing demand for IT to produce measurable business value. A recent survey by the Society of Information Management shows that the successful alignment of business and IT is a concern to top management. The inability to see fact-based views of IT activities frustrates management. An IT management solution should provide the visibility to bridge the gap between business and IT and should deliver transparent, integrated decision making processes to allocate IT resources wisely. Information technology is a resource that should be aligned with business objectives in order to benefit an organisation. In an attempt to improve our understanding of IT payoffs, this study uses a process-oriented model to assess the impacts of IT on key business activities within the value chain of the Sedibeng and Emfuleni local governments. The model includes corporate goals as an important context within which to evaluate IT payoffs. Executives play an increasing role in IT decisions and in recognition of these roles the objectives of this study are to: survey executives in the Sedibeng and Emfuleni municipalities on their goals for IT and their perceptions of realised IT payoffs. Evaluate executives' perceptions of payoffs from IT within the value chain to identify a relationship between corporate goals, IT and perceived IT payoffs. It is clear from the results obtained in this research that Sedibeng and Emhleni are unfocused organisations. This means that current goals for IT are not critical to any aspect of their business strategy. This study presents a graphical overview of perceived IT payoffs within the value chain for Sedibeng and Emfuleni municipalities. Customer relations activities appear as the lowest focus of IT business value whereas process planning and support activities are the primary focus.
Thesis (M.Sc. (Information Technology))--North-West University, Vaal Triangle Campus, 2007.